Learning challenges of nursing students in clinical environments: A qualitative study in Iran - Baraz, Shahram (J Educ Health Promot, 2015)
BACKGROUND: Clinical learning environment is a complex social entity. This environment is effective on the learning process of nursing students in the clinical area. However, learning in clinical environment has several benefits, but it can be challenging, unpredictable, stressful, and constantly changing. In attention to clinical experiences and factors contributing to the learning of these experiences can waste a great deal of time and energy, impose heavy financial burden on educational systems, cause mental, familial and educational problems for students, and compromise the quality of patient care. Therefore, this study was carried out with the goal of determining the learning challenges of nursing students in clinical environments in Iran. MATERIALS AND METHODS: In this qualitative study carried out in 2012–2013, 18 undergraduate nursing students were selected by using purposive sampling method from the Faculty of Nursing and Midwifery of Tehran and Shahid Beheshti Universities. Semi-structured interviews were used to collect data. The content analysis method was used to determine relevant themes. RESULTS: Two themes were derived from the data analysis, which represented the students’ clinical learning challenges. These two themes included insufficient qualification of nursing instructors and unsupportive learning environment. CONCLUSIONS: Identification of the students’ clinical learning challenges and actions to remove or modify them will create more learning opportunities for the students, improve the achievement of educational goals, provide training to nursing students with the needed competencies to meet the complex demands of caring and for application of theories in practice, and improve the quality of healthcare services.